Endangered Whales Still Get Tangled in Fishing Gear: Let’s Change the Way We Approach the Problem - Johnson, Tora (Maine Policy Review, 2023)
The Gulf of Maine lobster industry has been roiled by conflict over whale entanglement for decades. With fewer than 350 North Atlantic right whales remaining, federal regulators are again seeking to implement new measures to protect them from tangling in fishing gear, while the lobster industry faces myriad challenges. My 2005 book Entanglements examined the complex and fraught debate between whale advocates and fishermen. Each side believed the other was inherently evil, greedy, and unduly powerful. Of course, the truth lay somewhere between. Between them were the brave souls who went to sea to wrestle fishing gear off of entangled whales. It made for stirring narrative, but the inevitable conclusions of my book were less exciting. The federal Take Reduction Team (TRT) that was supposed to foster innovative solutions was ineffective. The National Marine Fisheries Service was besieged by lawsuits and plagued by distrust. My research revealed many reasons why the process failed: poor facilitation of the TRT, flawed federal laws obstructing feasible solutions, TRT ideas twisted into unworkable and unenforceable regulations that eroded trust, and a dearth of leaders who could quell the rancor. None of these realities has changed since, so renewed conflict was inevitable. In the intervening years, however, I have learned more about why such conflicts arise and persist and identified interventions that may help. This essay will offer insights from various sources that offer hope for both whales and fisheries if we embrace new ways of addressing the conflict, and if we act in time.